Pengaruh Latihan Interval dan Sirkuit Terhadap Daya Tahan Kardiovaskular Ditinjau dari Panjang Tungkai Siswa yang Mengikuti Ekstrakurikuler Atletik SDN Danau Sadar - Joni, Joni; Prastyawan, Rifky Riyandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze and explore various factors that influence cardiovascular endurance among students participating in the athletic extracurricular program at SDN Danau Sadar, with a focus on comparing two physical training methods, namely interval training and circuit training, as well as examining leg length as a moderating factor. This study employed a quasi-experimental design with a 2×2 factorial design. The population consisted of all students participating in the athletic extracurricular program at SDN Danau Sadar, totaling 32 students. The sample was selected using the 27% upper group and 27% lower group formula from the total population, resulting in 16 students. Data collection was conducted using the PACER test to measure cardiovascular endurance. Data analysis was performed using Two-Way ANOVA. The results of the study and analysis indicate that: (1) there is a significant difference in the effect of interval training and circuit training on cardiovascular endurance, as evidenced by an F value of 5.367 and a p value of 0.036 < 0.05. The circuit training group showed better cardiovascular endurance than the interval training group, with a posttest difference of 15.38; (2) there is a significant difference between short leg length and long leg length on cardiovascular endurance, as evidenced by an F value of 5.614 and a p value of 0.033 < 0.05. The long-leg group demonstrated better cardiovascular endurance than the short-leg group, with a posttest difference of 15.63; (3) there is no interaction between the type of training applied and leg length in influencing cardiovascular endurance, as evidenced by an F value of 0.379 and a p value of 0.550 > 0.05. In conclusion, circuit training is more effective than interval training in improving the cardiovascular endurance of students participating in the athletic extracurricular program, long leg length provides an advantage in cardiovascular endurance, and there is no interaction between training type and leg length in influencing cardiovascular endurance. Keywords: Athletics, Cardiovascular Endurance, Interval Training, Circuit Training, Leg Length